LITERATURE REVIEW: PERBANDINGAN EFEKTIVITAS TERAPI ULTRASOUND DIATHERMY DAN MICROWAVE DIATHERMY TERHADAP MOBILTAS PASIEN OSTEOARTRITIS LUTUT - Ahmad Sofian Tsauri; Muhammad Siddik; Didik Dwi Sanyoto; Bambang Dwi Putranto; Husna Dharma Putera (Homeostasis, 2022)
Osteoarthritis is a type of arthritis that is commonly found in the elderly and is the leading cause of pain in patients with knee osteoarthritis. Non-pharmacological therapy, such as ultrasound diathermy and microwave diathermy, is one of the treatment options. Thermal therapy and function in tissue regeneration, improving metabolic processes, and lowering inflammation of knee OA are two therapies that have something in common. The aim of the review is to compare the effectiveness of US and MWD on knee OA patients' mobility. analysis was carried out A literature study was conducted using several electronic medical journal databases, including PubMed-NCBI, ProQuest, Science Direct, and Google Scholar. Articles in English and Indonesian published between 2011–2021 qualify for inclusion. In this literature review, ten articles were used. The results of the review found that US and MWD have the same effectiveness in improving body function or mobility in knee OA patients. Six of the seven US articles showed effective results in improving the functional capacity of the body or mobility of knee OA. The three MWD articles also showed effective results in increasing the functional capacity of the body or the mobility of knee OA. Based on the average score of body functional parameters with WOMAC, TUGT, and stiffness, it can be concluded that MWD therapy is better than US in improving mobility function of knee OA